Pengaruh Azimuth terhadap Intensitas Cahaya, Tegangan, dan Arus Panel Surya 50 WP Off-Grid pada Program Match Fund Solar Cell UNTIRTA - Wahyu Alisia Pratama; Mohammad Fatkhurrokhman; Irwanto Irwanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
The adverse impact of fossil fuel use on the environment has prompted various parties to look for alternative solutions that are more environmentally friendly. One potential renewable energy source is solar energy. Solar panels, which function to convert solar energy into electrical energy, are the top choice because of their abundant abundance, clean nature, and ability to reduce dependence on fossil fuels. However, the performance of solar panels is affected by several factors, one of which is azimuth. The azimuth angle determines the orientation of the solar panel on the horizontal plane. The proper azimuth orientation helps to improve the overall efficiency of solar energy collection. A non-optimal azimuth angle can reduce the intensity of light received by the panel surface, thereby lowering the electrical voltage and the generated electric current. In off-grid systems, which rely entirely on solar energy to meet electricity needs, proper azimuth arrangement becomes crucial to ensure light absorption efficiency. From the results of the experiment, it was found that the influence of azimuth on light intensity, voltage and current was greater in the North position with a position of 0 degrees where a light intensity of 92000 lux, a voltage of 20.01 V, and a current of 2.0 A were obtained, so it can be concluded that the cardinal direction and angle can affect the intensity of light, electrical voltage and electric current obtained.